Clinical analysis of neuromyelitis optica spectrum disorders in childhood - Zhou, J (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2019)
Objective: To explore clinical features and the effect of treatment of neuromyelitis optica spectrum disorders (NMOSD) in childhood. Methods: Children who were hospitalized in Department of Pediatrics, Peking University First Hospital from January 2013 to June 2018 and meeting diagnostic criteria of NMOSD proposed by the International Panel for NMOSD Diagnosis in 2015 were summarized and followed up. The basic information, symptoms of each attack, locations and patterns of new lesions, features of cerebrospinal fluid, serologic markers, treatments and outcomes in these patients were analyzed. Thirty-three children were included in the study, with 13 males and 20 females. The median age of onset was 6.83 (4.25, 8.75) years. Compared aquaporin-4 immunoglobulin G (AQP4-IgG) associated NMOSD with myelin oligodendrocyte glycoprotein immunoglobulin G (MOG-IgG) associated NMOSD. Mann-Whitney U test was used for continuous variables and Fisher test for categorical variables in comparison between AQP4-IgG and MOG-IgG associated NMOSD. Wilcoxon test was used for annualized relapse rate (ARR) before and after adding disease-modifying drugs. Results: Optic neuritis (39% (13/33) in initial attacks and 49% (62/127) in total attacks) and myelitis (36% (12/33) in initial attacks and 26% (33/127) in total attacks) were the top two symptoms in both the initial attacks and all 127 attacks during follow-up. There was 42% (37/89) of brain magnetic resonance imaging (MRI) scans in acute phase showing new lesions in supratentorial white matter, with 43% (16/37) showing acute disseminated encepha lomyelitis (ADEM)-like or leukodystrophy-like patterns. AQP4-IgG was detected in 30% (10/33) patients, and MOG-IgG was detected in 55% (11/20) patients, with no combined positive case. In 20 patients treated with rituximab, two were treated after the initial attack. In the other 18 patients, the median annualized relapse rate decreased from 1.86 (1.52, 2.60) before treatment to 0.28 (0, 1.13) during treatment (Z=-3.376, P=0.001). Compared with AQP4-IgG associated NMOSD (10 cases), fever of unknown origin (8/40 vs. 0/33, P=0.007) was more common, area postrema syndrome (0/40 vs. 4/33, P=0.038) was fewer, cell count of cerebrospinal fluid (49.0 (17.5, 115.0) ×10(6)/L vs. 5.5 (3.0, 15.8)×10(6)/L, Z=-3.526, P=0.000) was higher in MOG-IgG associated NMOSD (11 cases). Conclusions: In childhood-onset NMOSD, optic neuritis and myelitis were top two symptoms. Childhood-onset NMOSD has high proportion of positive MOG-IgG. Lesions in supratentorial white matter are common. Rituximab could significantly decrease ARR of NMOSD in childhood. However, more studies should be conducted to explore the optimal treatment strategy in different antibody associated NMOSD